Development of Political Participation of People Samut Sakhon Province - Hauthong, Prasit; Niyomyah, Satit; Siriphornwut, Nattawat; Kalyanamitra, Kamolporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
The research aimed to 1) study the general conditions of political participation of people Samut Sakhon Province 2) study the factors that influenced political participation of people in Samut Sakhon Province 3) Find guidelines for developing of political participation of people Samut Sakhon Province. The research design was qualitative research. Twenty-five key informants were purposively selected and divided into four groups: Group 1, 10 representatives of eligible voters; Group 2, 5 representatives of community leaders; Group 3, 5 representatives of politicians; and Group 4, 5 experts. A semi-structured interview was used as the research tool. Key informants were interviewed face-to-face using in-depth interviews and documents. The collected data were analyzed for content. The research results: 1) The general condition of political participation found that. There was continuously interested and political movement, there was a process of political acculturation in, and there was a democratic political ideology. 2) Factors influencing of political participation. It was found all had an influence on political participation. 3) Guidelines for developing political participation should creating various public relations media both online and offline, support for the establishment and participation in political groups, have activities or projects that was new political approaches, create strong civic politics, have been an agency to monitor and inspect the performance of politicians, instill ideas, consciousness, volunteerism, and create political values. Article history: Received 14 April 2025 Revised 17 May 2025 Accepted 19 May 2025 SIMILARITY INDEX = 19.82 %